Adverse Husbandry of Maraena Whitefish Directs the Immune System to Increase Mobilization of Myeloid Cells and Proinflammatory Responses - Korytář, Tomáš; Nipkow, Mareen; Altmann, Simone; Goldammer, Tom; Köllner, Bernd; Rebl, Alexander (Frontiers in Immunology, 2016)
Adverse life circumstances evoke a common “conserved transcriptional response to adversity” (CTRA) in mammalian leukocytes. To investigate whether this pattern is preserved in lower vertebrates, maraena whitefish (Coregonus maraena) were exposed for nine days to different stocking densities: ~ 10 kg/m³ (low density), ~ 33 kg/m³ (moderate), ~ 60 kg/m³ (elevated), and ~ 100 kg/m³ (high). Transcriptome profiling in the liver and kidney of individuals from each group suggested that crowding conditions activate stress-related signaling and effector pathways. Remarkably, about one quarter of the genes differentially expressed under crowding conditions were involved in the activation of immune pathways such as acute-phase response and interleukin/TNF signaling attended by the simultaneous reduction of antiviral potency. Network analysis confirmed the complex interdigitation of immune- and stress-relevant pathways with interleukin-1 playing a central role. Antibody-based techniques revealed remarkable changes in the blood composition of whitefish and demonstrated the correlation between increasing stocking densities and elevated number of myeloid cells together with the increased phagocytic activity of peripheral blood leukocytes. In line with current studies in mammals, we conclude that crowding stress triggers in whitefish hallmarks of a CTRA, indicating that the stress-induced molecular mechanisms regulating the immune responses not only are conserved within mammals but were established earlier in evolution.